Climate sensitive growth model for volume and carbon storage of subtropical broadleaf secondary forests in China - Kailun Zou; Qigang Xu; Peng He; Xianzhao Liu (Ecological Indicators)
Studying the growth models of secondary forests is crucial for forest management in the context of climate change, particularly in the subtropical regions of China, where broadleaf secondary forests are both ecologically complex and abundant. This study employs an age-independent difference model, utilizing national continuous forest inventory data from Jiangxi and Hunan provinces to develop growth models for secondary forests. Climate variables are incorporated to simulate forest growth under different climate scenarios. The results indicate that both the growth potential and rate of secondary forests increase as secondary succession progresses. Mean Coldest Month Temperature (MCMT) and Mean Annual Precipitation (MAP) are significant climate factors, with forest volume increasing as MCMT and MAP rise, while carbon storage is primarily influenced by MCMT. In the context of climate change, the growth rate of secondary forests in the subtropical regions of China has significantly declined. Furthermore, the impact of climate change on forest volume and carbon storage exhibits spatiotemporal heterogeneity, with the degree of impact increasing from east (Jiangxi Province) to west (Hunan Province), resulting in a greater decline in growth rates in the west. This research provides scientific support for the management of secondary forests under future climate change scenarios.